(untitled) (Comparative & International Education Series, 2021)
Long viewed as insular and hesitant to employ foreign academics, a sharply declining birthrate has forced universities in Japan to change their approach, with new emphasis on international scholarship and English language degree programs appealing to international students. Foreign faculty hires and advancement have subsequently increased, though not without problems. To illustrate such changes, this chapter provides an overview of the Japanese university system and how the growing number of foreign faculty fit within it. As a parallel to increasing skilled labor migration to Japan, we consider the advantages and disadvantages for foreign academics working in Japanese institutions. Based on survey and anecdotal evidence, we find positive implications for foreign academics working in Japan, although questions of language, integration and work-life balance are in need of further consideration.